Public relations in the trust management. Prolegomena - Kaczmarczyk, Michał (Communication Today, 2025)
Trust management is a complex approach to internal and external relations within an organization, and to identiﬁ cation of strategic areas that govern such relations. Trust management operations are performed in various areas of managerial practice and form a sphere of activity that is related to human resource, knowledge and quality management. However, trust management is speciﬁ cally related to public relations of an organization. Trust management and PR are linked with each other through a number of functions and goals, as well as deployment tools. This paper attempts to present public relations as trust management. Such approach to PR reveals its essence. Contrary to an instrumental marketing approach, PR is not a set of promotional activities or activities that support promotion. It is the art of building and maintaining trust-based understanding between an organization and its surrounding environment.